Os novos quilombos: luta pela terra e afirmação étnica no Brasil [1988-2008] - Fiabani, Adelmir (Universidade do Vale do Rio do Sinos, 2008)
The thesis analyses the rural black community movement. It is also known like fugitive black slave movement (quilombola movement), from its beginning in the states of Maranhão and Pará until nowadays. This movement has begun in the end of 70s and gained impulse after being known the article 68 of the Transitory Constitutional Disposition Act, inside of Constitution of 1988. The black community has glimpsed the possibility of solution to the agrarian question through application of such constitutional article of law. For all the communities could be answered by this law, there was necessity of giving a new meaning to the word hiding place (quilombo). We should reflect on this process, because he has stimulated a great reflection about the nature of the rural black communities and has made possibilities about the same words to the ones of the 68 (sixty-eight) article. To understand the new meaning process, we have analysed the concept hiding place (quilombo) which was built during the history and its changes. W
Keywords: artigo 68; etnia; movimento quilombola; questão agrária; comunidades negras; agrarian question; article 68; ethnic; quilombola movement; black community; Ciências Humanas